A novel and robust heterogeneous Cu catalyst using modified lignosulfonate as support for the synthesis of nitrogen-containing heterocycles - Lai, Bingbing; Ye, Meng; Liu, Ping; Li, Minghao; Bai, Rongxian; Gu, Yanlong (Beilstein Journal of Organic Chemistry, 2020)
A waste biomass, sodium lignosulfonate, was treated with sodium 2-formylbenzenesulfonate, and the phenylaldehyde condensation product was then used as a robust supporting material to immobilize a copper species. The so-obtained catalyst was characterized by many physicochemical methods including FTIR, EA, FSEM, FTEM, XPS, and TG. This catalyst exhibited excellent catalytic activity in the synthesis of nitrogen-containing heterocycles such as tricyclic indoles bearing 3,4-fused seven-membered rings, 2‑arylpyridines, aminonaphthalenes and 3-phenylisoquinolines. In addition, this catalyst showed to be recyclable and could be reused several times without significant loss in activity during the course of the reaction process.
Keywords: biomass; heterogeneous catalyst; immobilized copper catalyst; lignosulfonate; nitrogen-containing heterocycles; solid acid